Tayangan Religi: Melekatnya Dunia Sosial dan Media Komersial - Amirudin Amirudin (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This article summarizes the results of ethographic research on Religious Shows as Cultural Production Field: Studies on religious show of Mamah and AA in Action. The purpose of this article is to explore how Mamah Dedeh as one of the actors in the cultural production process through religious shows plays her role from daily life that is related closely to religious criteria which her habitus is formed through the missionary on the social stage. Stage of da’wah which is purely colored by religious criteria as a “blackbox” that directs her preaching in moslem comunity. But then, after she entered da’wah system in the media stage, which contained market criteria that must be followed. How she mixes and embeds da'wah systems in the social world with da'wah in commercial media, it is a subject that interesting to discuss in this article.